5-weeks effect of beta-alanine supplementation in swimmers - Falcão , Luiz Eduardo Marinho (2023)
The scientific literature has demonstrated that the carnosine dipeptide appears to act by neutralizing hydrogen ions resulting from the dissociation of lactic acid, which may postpone the onset of fatigue following β-alanine (βA) intervention. For this, a study was drawn where the study participants were divided after randomization into two groups: placebo group (GPLA, n = 4) and β-alanine group (GBA, n = 5) where they received double-blind capsules with βA or placebo (1.6 g / day for the first week and 3.2 g / day for the next four weeks) associated with swimming tests (3 shots in 100 m free at 95% of HRMA). The results showed a reduction in the mean time of final GBA test (69.62 s vs. 69.51 s) when compared to GPLA (77.56 s vs. 77.89 s), but without significant differences (p > 0.05). There was only one change in lactate peak of GPLA compared to GBA in tests 2 and 3 (p <0.05). We found no significant differences after 5-week intervention on body composition and markers of hepatic and renal function in both groups. There was only one change in lactate peak of GPLA compared to GBA in tests 2 and 3 (p <0.05). It is concluded that the dosage of βA used in this study did not alter the athletic performance (end time of test) and body composition of the swimmers, however, it reinforced that the dosage used did not promote significant alterations in the hepatic and renal functions for a short time of intervention.